Análisis de la distribución de planta del camposanto Memorial Jardines de Santa Rosa, en la ciudad de Santa Rosa, en el 2024 - Palacios Miranda, Iván Steven (2026)
In this research, the plant distribution for a cemetery service of the Memorial Jardines de "San Pedro" consortium, a project located in a strategic place, was analyzed. The objective was to analyze, from an industrial perspective, the most suitable distribution for this service and to propose a design that integrates the wake, cremation, and cemetery services that do not currently exist in the area where the project is to be located. It was determined that there is a growing demand for this service, driven by the saturation of spaces in the municipal cemetery and the limited cultural shift toward more efficient, sustainable practices. The surveys applied to the population for the market study show the urgent need for a technical distribution of the areas that were determined, where priority was given to operational efficiency, reduction of the number of changes, and the incorporation of correctly dimensioned spaces to promote the comfort of the clients and to comply with the national norms and regulations. For this, the location of a plant by the Brown and Gibson location methodology was applied, obtaining the optimal location for the implementation of the cemetery, which turned out to be in the parish of Santa Rosa, El Oro; consecutively, a descriptive and field methodology known as Systematic Layout Planning was applied, with which the technical, operational and functional aspects of this service were established, the same aspects that were considered for the subsequent development of the distribution. Thanks to this study and the completion of all previous processes, an alternative physical distribution was developed based on the graph of activity relationships, and a computer drawing was created in AutoCAD for presentation.